(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Beyond the recurring questions "Is race social or biological?", "Is race real or illusory?" which encapsulate the philosophical morass of the ontology of race, this paper, after a brief summary of the development of the scientific debate, focuses on the attitude that the law should take towards this contested concept and the "cursed" word that describes it. In particular, the analysis will focus on a "symbolic" aspect, that of the use of the word "race" in the constitutional lexicon of different countries, and on a more "functional" one, related to the use of the "racial argument" in some policies aimed at overcoming health disparities. Lastly, a brief reference will be made to the impact of technological innovations on the racial discourse, to understand, in particular, whether and how A.I. technologies increase or reduce racial bias.